Accounting and Finance New Perspectives on Banking, Financial Statements and Reporting - Gharoie Ahangar, Reza; Öztürk, Can (IntechOpen, 2019)
Accounting and finance are common terms for users of financial information. Nowadays the reporting of financial as well as non-financial information of an entity, and efficiency in the banking system, are considered to be important issues by creditors, investors, and managers of financial markets.Over four sections this book addresses topics including national accounting standards and financial statement disclosure; foreign direct investment and the roles of accounting valuations and earnings management during the global financial crisis; and bankruptcy risk, banking efficiency, and debt restructuring in the United Nations General Assembly Resolution.